Co-Offending and Arrest: An Examination of the "Group Hazard" Hypothesis - Lantz, Brendan (Crime & delinquency, 2020)
Research on offending has long noted the prevalence of co-offending, and researchers have argued that an important component of the decision to co-offend is the risk of arrest. Following this, the current research examines the group hazard, or the risk of arrest associated with co-offending, using National Incident-Based Reporting System (NIBRS) data. Results indicate that there is a hazard for robbery and homicide, whereas there is a negative relationship between co-offending and arrest for assault. Furthermore, arrest risk also varies significantly according to the group size and the demographic composition of groups. Taken together, the results suggest that the relationship between co-offending and arrest is complex, and heterogeneity in the relationship may be an important explanation for the contradictory results found in previous research.